Three dimensional multi‐cellular muscle‐like tissue engineering in perfusion‐based bioreactors. Issue 1 (4th September 2015) - Cerino, Giulia; Gaudiello, Emanuele; Grussenmeyer, Thomas; Melly, Ludovic; Massai, Diana; Banfi, Andrea; Martin, Ivan; Eckstein, Friedrich; Grapow, Martin; Marsano, Anna
ABSTRACT: Conventional tissue engineering strategies often rely on the use of a single progenitor cell source to engineer in vitro biological models; however, multi‐cellular environments can better resemble the complexity of native tissues. Previous described co‐culture models used skeletal myoblasts, as parenchymal cell source, and mesenchymal or endothelial cells, as stromal component. Here, we propose instead the use of adipose tissue‐derived stromal vascular fraction cells, which include both mesenchymal and endothelial cells, to better resemble the native stroma. Percentage of serum supplementation is one of the crucial parameters to steer skeletal myoblasts toward either proliferation (20%) or differentiation (5%) in two‐dimensional culture conditions. On the contrary, three‐dimensional (3D) skeletal myoblast culture often simply adopts the serum content used in monolayer, without taking into account the new cell environment. When considering 3D cultures of mm‐thick engineered tissues, homogeneous and sufficient oxygen supply is paramount to avoid formation of necrotic cores. Perfusion‐based bioreactor culture can significantly improve the oxygen access to the cells, enhancing the viability and the contractility of the engineered tissues. In this study, we first investigated the influence of different serum supplementations on the skeletal myoblast ability to proliferate and differentiate during 3D perfusion‐based culture. We tested percentages of serum promoting monolayer skeletal myoblast‐proliferation (20%) and differentiation (5%) and suitable for stromal cell culture (10%) with a view to identify the most suitable condition for the subsequent co‐culture. The 10% serum medium composition resulted in the highest number of mature myotubes and construct functionality. Co‐culture with stromal vascular fraction cells at 10% serum also supported the skeletal myoblast differentiation and maturation, hence providing a functional engineered 3D muscle model that resembles the native multi‐cellular environment. Biotechnol. Bioeng. 2016;113: 226–236. © 2015 Wiley Periodicals, Inc. Abstract : This study describes the generation of engineered 3D multi‐cellular muscle‐like tissues in perfusion‐based bioreactors. Cerino and coworkers have investigated the role of different percentages of serum (20%, 10%, and 5%) on 3D skeletal myoblast maturation. After identifying the suitable serum percentage, they have co‐cultured skeletal myoblasts, as parenchymal cell source, and adipose tissue‐derived stromal vascular fraction cells, which include both mesenchymal and endothelial cells, to better resemble the native stroma.